A Procedure for Managing Conflict of Interest When Forming Thesis Juries - Williams-Jones, Bryn (BioéthiqueOnline, 2017)
Conflicts of interest in thesis juries, when not identified and appropriately managed, can lead to an uncritical and unfair evaluations that can then undermine trust in the process and threaten academic credibility and institutional reputation. This Commentary presents and justifies the choices made in developing a practical procedure to identify and manage conflicts of interest in the formation of Masters and PhD juries in the School of Public Health (ÉSPUM) at the University of Montreal.